The endocast of StW 573 ("Little Foot") and hominin brain evolution. Issue 126 (January 2019) - Beaudet, Amélie; Clarke, Ronald J.; de Jager, Edwin J.; Bruxelles, Laurent; Carlson, Kristian J.; Crompton, Robin; de Beer, Frikkie; Dhaene, Jelle; Heaton, Jason L.; Jakata, Kudakwashe; Jashashvili, Tea; Kuman, Kathleen; et al.
Abstract: One of the most crucial debates in human paleoneurology concerns the timing and mode of the emergence of the derived cerebral features in the hominin fossil record. Given its exceptional degree of preservation and geological age (i.e., 3.67 Ma), StW 573 ('Little Foot') has the potential to shed new light on hominin brain evolution. Here we present the first detailed comparative description of the external neuroanatomy of StW 573. The endocast was virtually reconstructed and compared to ten southern African hominin specimens from Makapansgat, Malapa, Sterkfontein and Swartkrans attributed to Australopithecus and Paranthropus . We apply an automatic method for the detection of sulcal and vascular imprints. The endocranial surface of StW 573 is crushed and plastically deformed in a number of locations. The uncorrected and therefore minimum cranial capacity estimate is 408 cm 3 and plots at the lower end of Australopithecus variation. The endocast of StW 573 approximates the rostrocaudally elongated and dorsoventrally flattened endocranial shape seen in Australopithecus and displays a distinct left occipital petalia. StW 573 and the comparative early hominin specimens share a similar sulcal pattern in the inferior region of the frontal lobes that also resembles the pattern observed in extant chimpanzees. The presumed lunate sulcus in StW 573 is located above the sigmoid sinus, as in extant chimpanzees, while it is more caudally positioned in SK 1585 and StW 505. The middle branch of the middle meningeal vessels derives from the anterior branch, as in MH 1, MLD 37/38, StW 578. Overall, the cortical anatomy of StW 573 displays a less derived condition compared to the late Pliocene/early Pleistocene southern African hominins (e.g., StW 505, SK 1585).